Hubungan antara Penggunaan AI terhadap Tingkat Pembelajaran Mahasiswa - Moch Alfiana Candra Jani; Najla Khayira; Sandra Siti Nurjanah; Mia Lasmi Wardiyah (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
The integration of Artificial Intelligence (AI) in education has introduced a more responsive and personalized learning approach. This study aims to examine the correlation between the intensity of AI usage and students’ learning outcomes. Employing a quantitative approach, the research utilized Pearson Product Moment correlation analysis. A total of 27 students, selected through purposive sampling and known to actively use AI in their learning process, participated in the study. Prior to the correlation analysis, the data underwent validity, reliability, normality, homogeneity, and linearity testing. The results confirmed that the instrument met the criteria for validity and reliability (Cronbach’s Alpha = 0.824), with data distribution being normal and homogeneous, and the relationship between variables being linear. The Pearson correlation coefficient of r = 0.583 with a significance value of p = 0.001 indicates a statistically significant and moderately strong positive relationship. These findings suggest that AI plays a meaningful role in enhancing students’ learning effectiveness. Therefore, it is essential to provide guidance and development efforts to ensure AI is utilized ethically and educationally to optimize its impact in academic settings.